Water-based organic zinc-rich coatings with excellent hydrogen production suppression capabilities

CN122580384APending Publication Date: 2026-08-14LUOBA LUO CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480083875.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-01-16
Filing Date
2024-12-26
Publication Date
2026-08-14

AI Technical Summary

Technical Problem

[0008]但是,水性富锌涂料与非水性且非富锌系的涂料的前提构成根本不同,难以将该防锈颜料单纯地应用于水性富锌涂料

Benefits of technology

能够实现防腐蚀性,并且能够实现涂料液中以及涂布后的未干燥涂膜中的氢气产生抑制效果。由此,也可以看出一液型的水性富锌涂料的可能性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

A water-based zinc-rich coating is provided, which can suppress hydrogen production and achieve low toxicity and high corrosion resistance to steel and the like. The solid components contain at least 70% by weight of zinc powder and at least 0.02% by weight of vanadium compound, and further contain a binder resin, wherein the binder resin constitutes at least 20% by weight of the portion excluding zinc powder and vanadium compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to waterborne organic zinc-rich coatings with excellent hydrogen generation suppression capabilities. Particularly, it relates to waterborne coatings that provide corrosion protection (especially heavy-duty corrosion protection) when applied to steel surfaces, comprising zinc powder and a binder resin. Furthermore, specifically, it relates to waterborne zinc-rich coatings capable of achieving hydrogen generation suppression capabilities. Background Technology

[0002] Zinc-rich coatings (zinc-rich paints) are used as anti-corrosion coatings for steel products, especially after structural materials exposed to the outdoors are installed, and as heavy-duty anti-corrosion coatings for repairing and regenerating anti-corrosion films (Non-Invention Patent Document 1). Regarding zinc-rich coatings, the following is described at the beginning of the main text (excluding the gist) of Non-Invention Patent Document 1.

[0003] Zinc-rich coatings (zinc-rich paints) refer to "undercoatings containing a large amount of zinc powder (70-90 wt% in the coating film). They are used as shop primers for steel used in ships or bridges, as well as as anti-corrosion undercoatings to protect large steel structures such as bridges or factories from corrosion." Zinc-rich coatings contain zinc powder and a binder, and may include additives as needed. In particular, in recent years, water-based zinc-rich coatings with low VOC (volatile organic compounds) content and the ability to dry and cure at room temperature have been well received (Patent Documents 1-4). In Patent Document 1, a coating is illustrated that uses a water-based polyurethane resin as a binder and a small amount of micronized silica and a small amount of tackifier ("polyether polyol and nonionic surfactant", etc.) as additives.

[0004] On the other hand, hydrogen gas may be generated after the water-based zinc-rich coating is formulated due to the reaction between water and zinc powder. Therefore, under coating conditions such as high humidity and time required for coating film drying, hydrogen gas may be generated in the coating film after surface drying at areas such as joints or steps of the steel where the film thickness is excessive, potentially causing coating defects (Patent Document 2). Therefore, in the embodiments of Patent Document 2 described below, the use of "free acid of alkyl phosphate ester compound", "free acid of alkyl / allyl phosphate ester compound", "alkyl alkoxide ammonium salt of copolymer containing phosphate ester group" and "sulfonate ester compound" as "adhesion promoters" is disclosed.

[0005] In the technology using an "adhesion promoter" in Patent Document 2, the ability to inhibit hydrogen generation is insufficient. There are concerns about coating defects and appearance abnormalities caused by hydrogen generation when the material is placed in a high humidity environment with a relative humidity approaching 100% for extended periods. Furthermore, the applicability period of approximately one week cannot be guaranteed.

[0006] On the one hand, in the technology of Patent Document 3, there is an example of using phosphate or tripolyphosphate to suppress hydrogen production, but in this case, the ability to suppress hydrogen production is not sufficient. For example, compared to the hydrogen production during the applicability period of about one week, there is a problem of quality reduction.

[0007] On the other hand, while chromate-based compounds are used in anti-corrosion coatings for galvanized steel sheets that do not employ zinc-rich coatings, research is underway to replace them with non-chromate-based compounds (Non-Invention Patent Documents 2-3). Table 2-1 of Non-Invention Patent Document 2 shows that hexavalent chromate-based compounds exhibit particularly superior anti-corrosion performance compared to phosphorus vanadate, phosphorus molybdate, etc. Furthermore, Non-Invention Patent Document 2 states that good performance was obtained by using vanadium pentoxide, calcium phosphate, and / or calcium silicate as anti-rust pigments. Additionally, Non-Invention Patent Document 3 confirms the corrosion resistance of vanadium-based coatings.

[0008] However, the composition of water-based zinc-rich coatings is fundamentally different from that of non-water-based and non-zinc-rich coatings, making it difficult to simply apply this anti-rust pigment to water-based zinc-rich coatings.

[0009] For example, when strontium chromate is applied to water-based zinc-rich coatings, although it can suppress hydrogen production, its important sacrificial corrosion protection is hindered, resulting in a significant reduction in corrosion resistance. In short, it is generally difficult to achieve both the rust prevention properties of zinc and the suppression of hydrogen production.

[0010] Existing technical documents Invention Patent Documents Invention Patent Document 1: Japanese Patent No. 5750318 Invention Patent Document 2: Japanese Patent Application Publication No. 2020-026457 Invention Patent Document 3: Japanese Patent Application Publication No. 2021-134228 Invention Patent Document 4: Japanese Patent Application Publication No. 2013-221081 Non-invention patent literature Non-invention patent literature 1: "Durability and Corrosion Prevention Lecture (Lecture 5): Fundamentals and Recent Topics of Zinc-Rich Paints", J.Jpn. Soc. Colour Mater., 88(2) (2015) (https: / / www.jstage.jst.go.jp / article / shikizai / 88 / 2 / 88_51 / _pdf) Non-invention patent document 2: "Development of a novel anti-rust pigment for coated steel sheet and explanation of the anti-corrosion mechanism of a sacrificial anti-corrosion coating system", Hideki Matsuda, doctoral dissertation at Hiroshima University (https: / / ir.lib.hiroshima-u.ac.jp / 00044628) Non-invention patent document 3: "Research on chemically formed film on zinc plating using chromium as a metal substitute", Tetsuto Kajiyama, Research Report No. 4, Tokyo Metropolitan Research Center for Industrial Technology, 2009, pp. 72-73 (https: / / www.iri-tokyo.jp / uploaded / attachment / 836.pdf) Non-invention patent document 4: "Waterborne Robal | Robal Co., Ltd." (https: / / www.roval.co.jp / products / aqua / howto.html) Summary of the Invention

[0011] The problem that the invention aims to solve In water-based zinc-rich coatings, it is desirable to suppress hydrogen production and achieve coatings with low toxicity and high corrosion resistance. In particular, such coatings are expected to be cost-effective and easy to apply.

[0012] On the other hand, as described in, for example, non-patent document 4, water-based zinc-rich coatings are applied after mixing "zinc powder" and "coating liquid". The option with a longer pot life (potential life) after mixing is preferred in practice. While the pot life decreases due to the generation of hydrogen gas based on the reaction of water and zinc, a pot life of approximately one week is desired by customers.

[0013] We have repeatedly and thoroughly studied the potential of zinc-rich coatings containing zinc powder as a business for the company, and found that by adding specific inorganic additives to water-based zinc-rich coatings, it is possible to effectively suppress hydrogen production while maintaining high corrosion resistance.

[0014] Methods for solving problems In a preferred embodiment, relative to the dried coating film (the solid component of the coating), the water-based zinc-rich coating may contain at least 70% by weight, preferably 80% by weight, more preferably 90% by weight, further preferably 93% by weight, even more preferably 94% by weight, and even more preferably 95% by weight, and less than 98% by weight or less than 97% by weight, for example, containing 80 to 98% by weight or 90 to 97% by weight.

[0015] In addition, relative to the dried coating film (the solid component of the coating), the vanadium compound is at least 0.02% by weight or more, preferably 0.05% by weight or more, more preferably 0.1% by weight or more, and even more preferably 0.2% by weight or more. There is no particular upper limit, but from the point of view of cost, it is preferable to be 5% by weight or less.

[0016] Furthermore, the dried coating film (the solid component of the coating) contains at least 20% by weight, preferably 30% by weight, more preferably 40% by weight, further preferably 50% by weight, even more preferably 60% by weight, and still more preferably 70% by weight or 80% by weight, excluding zinc powder and vanadium compounds. For example, it may contain 70-99% by weight or 70-100% by weight. It should be noted that the content of the binder resin refers to the content of the resin polymer itself.

[0017] The vanadium compound is at least one of vanadate or vanadate. It should be noted that there are many types of vanadium compounds, but few are considered to have an effective effect in inhibiting hydrogen production. Furthermore, many are believed to reduce the activity of zinc and decrease the storage stability of coatings. Preferred substances include strontium vanadate as a vanadate and vanadium pentoxide as a vanadate. However, due to the numerous legal restrictions on vanadium pentoxide, which make it difficult to implement, strontium vanadate is more preferred.

[0018] It should be noted that the average particle size (D) of the primary particles of vanadium compounds 50 The preferred size is 1~20μm or 1~10μm, and in particular it can be 2~8μm.

[0019] When the vanadium compound is strontium vanadate, the strontium vanadate content in the dried coating film (solid component of the coating) is at least 0.05% by weight, more preferably 0.1% by weight, and particularly 0.2% by weight or more. There is no particular upper limit, but from a cost point of view, it is preferable to be 5% by weight or less.

[0020] On the other hand, when the vanadium compound is vanadium pentoxide, in the dried coating film (the solid component of the coating), vanadium pentoxide is at least 0.02% by weight or more, preferably 0.05% by weight or more, more preferably 0.1% by weight or more, even more preferably 0.2% by weight or more, and for example, it is desirable to be 0.5% by weight or less.

[0021] In one embodiment, the binder resin may be included in the coating along with zinc powder or the like, in the form of a resin liquid dispersed or dissolved in a solvent containing water or a partially organic solvent. As examples of preferred binder resins, organic and inorganic systems are not particularly limited, but as a general film-forming resin, it may be any one or a combination of two or more selected from acrylic resins, epoxy resins, polyurethane resins, epoxy ester resins, etc. It should be noted that the curing method of the binder resin may be either a one-component or a two-component type, but a one-component type is preferred from the viewpoint of coating workability.

[0022] Depending on the circumstances, water-based zinc-rich coatings can be inorganic or organic-inorganic composite coatings that contain alkyl silicates, basic silicates, etc., as binders.

[0023] The average particle size (D) of primary particles in zinc powder 50 The preferred diameter is 1~20 μm, more preferably 1~10 μm, and particularly preferably 2~8 μm. The zinc content in the zinc powder is at least 90% by weight, for example, 94% by weight or more or 95% by weight or more.

[0024] In a preferred embodiment, the water-based zinc-rich coating can include additives to improve corrosion resistance in the dried coating film (the solid component of the coating) as needed. These additives can be appropriately selected from molybdate-based, tungstate-based, nitrite-based, phosphate-based (phosphate, calcium phosphate, magnesium phosphate, condensed phosphates), tannic acid-based, thiourea-based, and benzotriazole-based formulations.

[0025] Invention Effects It can achieve corrosion resistance and suppress hydrogen generation in the coating liquid and in the undried coating film after application. This also demonstrates the potential of one-component water-based zinc-rich coatings. Detailed Implementation

[0026] In one embodiment, water-based zinc-rich coatings can be easily applied to metal surfaces or walls using ordinary coating rollers or brushes, and can dry in, for example, less than 30 minutes or less than 1 hour by simply leaving (standing) at room temperature (typically 15 to 25°C, e.g., 23°C).

[0027] This type of water-based zinc-rich coating can be easily applied to indoor or outdoor iron frames, iron plates, iron columns, handrails, door handles, and door levers after construction. It can also be applied to walls, fences, columns, shelves, and storage boxes. From the viewpoint of achieving corrosion protection, it is preferably used on steel products, but it can also be used on products made of other metals such as aluminum, or even products made of non-metallic materials.

[0028] Example The embodiments and comparative examples of this application confirm the ability to suppress hydrogen production and the rust prevention properties.

[0029] The coatings used to confirm the ability to suppress hydrogen production and prevent rust are as follows (1) to (3).

[0030] (1) Examples and Comparative Examples 1-7 • Adhesive resin: One-component waterborne polyurethane resin (Superflex 150, a polyurethane aqueous dispersion manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.) • Hydrogen suppression additives: strontium vanadate or vanadium pentoxide.

[0031] • The content (by weight) of hydrogen suppression additives (vanadium compounds) in the dried coating film (solid component of the paint) is: 0.01, 0.02, 0.05, 0.1, 0.2, 0.5, 1, 2 or 5.

[0032] • Zinc content in the dried coating (solid component of the paint): Zinc powder is added to bring the content to 93% by weight. (The portion excluding the solid component of zinc powder and hydrogen suppressant additives is 7% by weight.) • In the dried coating film (the solid component of the paint), a binder resin is added to make it 95% by weight of the portion excluding zinc powder and vanadium compounds.

[0033] • A substance in which water is added at a weight ratio of 85:15 of the above solid components is used as a coating.

[0034] (2) Comparative Examples 8-13 Regarding the hydrogen suppression additive, except for the changes described below, the same composition as in the Examples and Comparative Examples 1-7 was used.

[0035] • Comparative Example 8: No additives.

[0036] • Comparative Examples 9 and 10: Strontium chromate was added, so that its content in the dried coating film (solid component of the paint) was 0.1% by weight and 0.2% by weight, respectively.

[0037] • Comparative Examples 11 and 12: Magnesium vanadate was added, so that its content in the dried coating film (solid component of the coating) was 0.1% by weight and 0.2% by weight, respectively.

[0038] • Comparative Examples 13 and 14: Calcium vanadate was added, so that its content in the dried coating film (solid component of the paint) was 0.1% by weight and 0.2% by weight, respectively.

[0039] • Comparative Examples 15 and 16: Aluminum vanadate was added, so that its content in the dried coating film (solid component of the coating) was 0.1% by weight and 0.2% by weight, respectively.

[0040] (3) Comparative Examples 17 and 18 The coating was prepared with reference to embodiments in existing technical literature.

[0041] • Comparative Example 17: A coating was prepared with reference to Example 13 of Patent Document 2.

[0042] • Comparative Example 18: A coating was prepared with reference to Example 7 of Patent Document 3.

[0043] <Steps for confirming hydrogen production inhibition capability> The confirmation of hydrogen production suppression capability is carried out according to the following steps.

[0044] 1. Coating was added to an aluminum bag that could seal hydrogen gas. After the aluminum bag was sealed with heat, the volume of the aluminum bag (volume before the test) was determined using the Archimedes method.

[0045] 2. After the aluminum bags were left to stand at 45°C for 7 days (Table 1) or 3 months (Table 2), the volume of the aluminum bags (volume after the test) was determined using the Archimedes method.

[0046] 3. Calculate the volume expansion rate using the following formula.

[0047] Volume expansion rate = (Volume after test / Volume before test - 1) × 100% <Confirmation of Hydrogen Production Inhibition Capability> The results confirming the ability to suppress hydrogen production are shown in Tables 1-2 below.

[0048] Here, a volume expansion rate less than 100% is set to "〇", and a volume expansion rate greater than 100% is set to "×". It should be noted that the test is conducted with a sample size of n=2. When the result is "×, ×", it is evaluated as "×", when the result is "×, 〇", it is evaluated as "△", and when the result is "〇, 〇", it is evaluated as "〇".

[0049] <Steps to confirm rust prevention> The rust resistance is confirmed by following these steps.

[0050] 1. Store the prepared coating in a constant temperature bath set at 45°C for 7 days (Table 1) or 3 months (Table 2), then stir, apply the coating to the steel plate to make the dry film thickness 80μm, and dry at room temperature for 1 week.

[0051] 2. Immerse in the salt spray test (hereinafter referred to as SST) for 480 hours (Table 1; test on coated steel sheets made with paint after 7 days of storage at 45°C) or 800 hours (Table 2; test on coated steel sheets made with paint after 3 months of storage at 45°C).

[0052] <Evaluation Criteria for Rust Prevention> The results confirming the rust prevention properties are shown in Table 1 below.

[0053] Here, samples from which no red rust is observed at the cut are designated as "〇", and samples from which red rust is observed at the cut are designated as "×". It should be noted that the test is conducted with a sample size of n=2. The result of "×, ×" is evaluated as "×", the result of "×, 〇" is evaluated as "△", and the result of "〇, 〇" is evaluated as "〇".

[0054] As shown in Table 1, in Examples 1-7 where strontium vanadate was added in the range of 0.05-5% by weight, excellent results were obtained in both hydrogen generation suppression and rust prevention. On the other hand, in Comparative Examples 1-2 where the amount of strontium vanadate added was less than that in Example 1, the hydrogen generation suppression was not necessarily sufficient.

[0055] As shown in Table 1, in Examples 3, 8-11, which contained 0.2% by weight of strontium vanadate, excellent results were obtained in both hydrogen generation suppression and rust prevention. On the other hand, in Comparative Example 3, where the combined zinc content and vanadium compound concentration were lower than in Example 11, the rust prevention was not necessarily sufficient.

[0056] Furthermore, as shown in Table 1, in Examples 12-16 where vanadium pentoxide was added in the range of 0.02-0.5% by weight, excellent results were obtained in both hydrogen generation suppression and rust prevention. On the other hand, in Comparative Example 4, where the amount of vanadium pentoxide added was less than that in Example 12, the hydrogen generation suppression was insufficient. In addition, in Comparative Examples 5-7, where the amount of vanadium pentoxide added was greater than that in Example 16, the rust prevention was not necessarily sufficient.

[0057] As further shown in Table 1, in Comparative Example 8, which did not contain any vanadium compounds or other additives, although the rust prevention was excellent, it of course did not show any ability to suppress hydrogen production.

[0058] On the other hand, in Comparative Examples 9 and 10, where strontium chromate, an additive considered to have excellent rust-preventing properties, was added instead of vanadium compounds, although the ability to suppress hydrogen production was sufficient, the rust-preventing properties were insufficient.

[0059] In addition, in Comparative Examples 11-16, where other vanadates (magnesium vanadate, calcium vanadate, aluminum vanadate) were added to replace vanadium compounds, the ability to suppress hydrogen production and the rust prevention were both insufficient.

[0060] Based on the results of Comparative Examples 9-16, excellent results were obtained only when a specific vanadium compound was used, among additives that are considered general rust inhibitors.

[0061] It should be noted that certain vanadium compounds (i.e., strontium vanadate and vanadium pentoxide) are considered to differ from other vanadates because of their different solubilities in water and the different oxidizing power of the dissolved components.

[0062] Table 2 presents the test results of the hydrogen generation suppression ability of the coating after storage at 45°C for 3 months, and the additional test results of an 800-hour salt spray test on coated steel plates made using the same coating after storage at 45°C for 3 months. As shown in Table 2, the composition of the coatings in Examples 17-22 is the same as that in Examples 10, 9, and 1-4, respectively. In addition, in Examples 23-30, the concentration of strontium vanadate in the solid components of the coatings is the same as that in Examples 19-22 (which have the same composition as Examples 1-4, respectively). However, the zinc content in the solid components of the coatings is 94% by weight in Examples 23-26 and 95% by weight in Examples 27-30.

[0063] As shown in Table 2, in Examples 18, 20-22, 24-26 and 29-30, after being stored at 45°C for 3 months, the zinc content in the solid components of the coating was 90% by weight or more, and the concentration of strontium vanadate in the solid components of the coating was 0.1% by weight or more, good results in hydrogen generation suppression and corrosion resistance were also obtained.

[0064] In contrast, in Example 17 (with the same composition as Example 10), where the zinc content in the solid component of the coating is 80% by weight, the hydrogen generation suppression ability is good due to the strontium vanadate concentration of 0.2% by weight, but the rust prevention performance is insufficient. Furthermore, in Examples 19, 23, and 27, where the strontium vanadate concentration in the solid component of the coating is 0.05% by weight, the hydrogen generation suppression ability is insufficient, and therefore, the rust prevention performance is also insufficient.

[0065] As further shown in Table 2, in Comparative Example 19 (which has the same composition as Comparative Example 8) without the addition of strontium vanadate, the ability to suppress hydrogen generation is insufficient, and the rust prevention performance is also insufficient.

[0066] Comparing the results in Table 1 and Table 2, it was found that the necessary concentrations of zinc powder and strontium vanadate in the solid components of the coating can vary depending on the storage period, storage conditions, and required rust-preventive properties. Specifically, the minimum necessary concentration of zinc powder was found to vary from 70% to 90% by weight, and the minimum necessary concentration of strontium vanadate was found to vary from 0.05% to 0.2% by weight.

Claims

1. A water-based zinc-rich coating comprising at least 70% by weight of zinc powder and at least 0.02% by weight of vanadium compound in its solid components, and comprising a binder resin in its solid components, wherein the binder resin comprises at least 20% by weight of the portion excluding zinc powder and vanadium compound.

2. The water-based zinc-rich coating according to claim 1, wherein, The vanadium compound is composed of at least one of strontium vanadate and vanadium pentoxide.

3. The water-based zinc-rich coating according to claim 1, wherein, The vanadium compound is strontium vanadate.

4. The water-based zinc-rich coating according to claim 1, wherein, The solid composition contains more than 90% by weight of zinc powder and more than 0.1% by weight of strontium vanadate.

5. A coating product coated with any one of claims 1 to 4.

Citation Information

Patent Citations

  • Two phase pulse receiving circuit

    JP1982050318B2

  • Normal temperature-drying type aqueous zinc-rich coating material, and method for coating the same

    JP2013221081A

  • Coating material composition, corrosion prevention method and coated body

    JP2020026457A

  • Aqueous organic zinc-rich coating composition

    JP2021134228A